Establishing a focus in sport psychology within a clinical psychology doctoral program: Reflections from a pilot year. Issue 2 (3rd May 2016) - Perry, Joanne; Ross, Michael
ABSTRACT: Sport psychology consultation and clinical psychology practice are becoming increasingly related, which necessitates the creation of applied sport psychology training opportunities for clinical psychology graduate students. Recent education and training guidelines in professional psychology identify sport psychology as an APA proficiency that can be integrated as a "focus" in graduate training programs. This article discusses an inaugural year of an applied sport psychology training opportunity within a university's athletic department, including a detailed description of the experience and an evaluation of services. This article seeks to provide guidance for training programs interested in establishing a focus in sport psychology.